Optimization of Mocaf Red Bean Composite Flour Ratios for Improving the Chemical, Texture, and Sensory Quality of Pie Crust - Roro Wasita; Pudji Astuti (Universitas Negeri Padang, 2026)
This study aimed to determine the effect of mocaf and red bean flour ratios on the chemical characteristics, color, texture, and sensory acceptance of pie crust. This research was conducted using an experimental method with four treatment ratios of mocaf flour and red bean flour, namely F0 100:0, F1 70:30, F2 60:40, and F3 50:50. The observed parameters included hedonic evaluation of color, aroma, texture, taste, and overall acceptance involving 42 panelists, color analysis using a Chroma Meter CR-400, texture analysis using a Texture Analyzer, and chemical analysis consisting of moisture and protein content. Hedonic data were analyzed using the Kruskal–Wallis test and followed by the Mann–Whitney test when significant differences were found. The results showed that F2 obtained the highest sensory scores for color 7.95, aroma 7.95, texture 8.21, taste 7.98, and overall acceptance 8.33. Significant differences were observed in texture and overall acceptance among treatments. Increasing the proportion of red bean flour decreased lightness and yellowness values, while redness increased. The moisture content ranged from 6.84% to 8.51%, with the lowest value found in F2. Protein content increased from 1.56% in F0 to 8.71% in F3. Treatments F1, F2, and F3 met the minimum protein requirement based on SNI 2973:2022, while all treatments still had moisture content above the maximum standard limit. Based on sensory, chemical, color, and texture characteristics, F2 was the most balanced formulation for producing pie crust made from mocaf and red bean flour.